Cittadinanze nella storia dello Stato contemporaneo - Aglietti, Marcella (Temi di storia - Open Access, 2017)
Cittadinanze offers a new perspective on the history of the State, understood in the aristotelian sense as the whole of its citizens. The volume contains twelve essays dedicated to the possible ways in which citizenship took shape during the contemporary age, analyzing the various historical concretions. Not a single, but a plural citizenship, an object and an epistemological instrument of many declinations - institutional, theoretical-political, juridical, philosophical. A reconstruction conducted through different places and times, ranging from the French and American revolutions to the immateriality of the digital divide. An original exam that interrogates the stories, practices and symbols that have linked individuals to their political communities.